2019
DOI: 10.1177/0954405419828590
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing of high-strength weathering steel parts fabricated by gas tungsten arc: Microstructure and mechanical properties

Abstract: This study focuses on microstructure and mechanical properties as a function of location in additively manufactured high-strength weathering steel components using gas tungsten arc as the heat source. Variations of microstructure and mechanical properties in various locations are presented and analysed. The as-deposited high-strength weathering steel is composed of columnar grain morphology with proeutectoid ferrite, acicular ferrite, side plate ferrite and a small amount of pearlite microstructure in the top … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…After sintering, the alumina crystal particles were grown gradually and connect together through strong interaction forces during the sintering process, which lead to the similar shrinkage of the sintered ceramics. [56][57][58]…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…After sintering, the alumina crystal particles were grown gradually and connect together through strong interaction forces during the sintering process, which lead to the similar shrinkage of the sintered ceramics. [56][57][58]…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Many researches on low‐carbon steel fabricated through WAAM using different depositing strategies have reported that the microstructures of low‐carbon low‐alloy steel are significantly influenced by their unique thermal histories. [ 25–29 ] However, there are few studies on the microstructure of steel fabricated through WAAM using a water bath. In this study, a low‐carbon low‐alloy steel sample is fabricated through GAM‐WAAM using the modified water‐bath method with a changing level as the active cooling approach to realize a high cooling rate, and another sample is fabricated under air cooling for comparison.…”
Section: Introductionmentioning
confidence: 99%
“…As for other metal alloys, such as weathering steel, Ni-Ti structure, Inconel-718 alloy, Ni/Febased superalloy, and some other Al alloy have also been studied by some other researchers. [7][8][9][10] Olakanmi et al studied aluminum alloy powder. 11 The process parameters were changed to optimize the microstructure of the parts and different properties of the printed parts can be found in this work.…”
Section: Introductionmentioning
confidence: 99%